2018
DOI: 10.1016/j.sdentj.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between skeletal maturation and developmental stages of canines and third molars among Saudi subjects

Abstract: Dental developmental stages were highly correlated with CVM stages III and IV among Saudi subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…There are other methods [ 4 , 8 , 37 , 38 ] of estimating age based on the growth of the cervical vertebrae, wrist, or finger bones. A positive correlation between bone growth and the state of dental maturation has been shown in numerous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other methods [ 4 , 8 , 37 , 38 ] of estimating age based on the growth of the cervical vertebrae, wrist, or finger bones. A positive correlation between bone growth and the state of dental maturation has been shown in numerous studies.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on what is the best method to predict chronological age [ 3 ]. Bone growth evaluation has been used on wrist radiographs [ 4 , 5 ] or according to the stages of maturation of the cervical vertebrae [ 6 – 8 ]. Currently, one of the most commonly used methods to estimate chronological age is the calculation of dental age through the mineralization phases of the teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, significant gender‐based differences were detected with the Demirjian and Nolla methods (Hegde et al, 2017). Males had slightly higher correlation between skeletal cervical vertebral maturity stages and left mandibular canine developmental stages in a Saudi population (Al‐Balbeesi et al, 2018). Contradictory to this study, the estimation errors of the above methods were found to be greater in males than in females (Melo & Ata‐Ali, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The dental literature has no scarcity for research related to correlation between dental calcification stages and skeletal maturation stages. But these studies have the following shortcomings: (a) lack of sample size calculation [ 14 21 ], (b) very small sample size [ 17 ], (c) evaluation of maxillary teeth while they are superimposed by other structures [ 22 ], (d) wide age range (patient age greater than 16 years) [ 19 , 20 ], and (e) inclusion of teeth at the age where root formation either has not yet started or has already been completed [ 14 , 18 20 ]. A systematic review and meta-analysis [ 23 ] also pointed out methodology errors and high heterogeneity in the published on this topic research.…”
Section: Introductionmentioning
confidence: 99%